1977
DOI: 10.1161/01.str.8.4.468
|View full text |Cite
|
Sign up to set email alerts
|

Doppler cerebrovascular examination: improved results with refinements in technique.

Abstract: SUMMARY Doppler ultrasonic assessment of extracranial carotid occlusive disease has been modified to decrease the incidence of false positive and negative diagnoses. The technique, which assessed directional flow in the frontal artery and the influence of sequential compression of each temporal, infraorbital, facial and common carotid artery, was performed on 152 vessels visualized by contrast arteriography. Presence or absence of significant (> 50%) stenosis or occlusion of the internal carotid artery was ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

1978
1978
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(13 citation statements)
references
References 5 publications
1
11
0
1
Order By: Relevance
“…If flow is in a reverse direction and if it diminishes or stops with compression of the feeding branches, the test is positive. To further evaluate other potential sources of collateral flow, Barnes et al 22 have proposed compression of the ipsilateral and contralateral common carotid arteries low in the neck.…”
Section: Indirect Testing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If flow is in a reverse direction and if it diminishes or stops with compression of the feeding branches, the test is positive. To further evaluate other potential sources of collateral flow, Barnes et al 22 have proposed compression of the ipsilateral and contralateral common carotid arteries low in the neck.…”
Section: Indirect Testing Methodsmentioning
confidence: 99%
“…Using all the compression maneuvers, Barnes et al 22 reported a 95% accuracy in detecting high grade stenoses (greater than 50% diameter reduction) and total occlusions (36 sides evaluated). On the other hand, the test was negative in 51 normal carotid arteries and in 59 of 63 patients with plaques that narrowed the carotid artery by less than 50%.…”
Section: Indirect Testing Methodsmentioning
confidence: 99%
“…The diagnosis of altered internal carotid artery perfusion due to ob structive lesions can be made as well as inferences regarding patterns of collateral flow. 29 ' 43 - 44 Localiza tion of the site of an obstruction is not possible and multiple lesions in the same artery can not be recog nized. The reported accuracy with this technique var ies significantly, and it appears that of all noninvasive testing methods this is the most dependent upon opera tor experience and skill.…”
Section: -42mentioning
confidence: 99%
“…6 We recently developed a simple and safe method Received August 15, 1988; accepted February 1, 1989. for OAP determination, called ophthalmomanometryDoppler (OMD). 7 Based on Doppler ultrasound principles, OMD provides simultaneous information about both the maximum perfusion pressure and the flow direction in the ophthalmic circulation.…”
mentioning
confidence: 99%